Allocation of Cash Flows in Unionized Firms. Issue 4 (3rd April 2017) - Lee, Woo-Jong; Oh, Seungbin; Yim, Sang-Giun; Yu, Kyunghwa
ABSTRACT: How do unionized firms use cash inflows? To answer this hitherto unexplored question, we adopt the system of equations developed by Dasgupta, Noe, and Wang (2011) to explicitly address possible interdependence of cash allocation decisions in unionized firms. Based on comprehensive firm-level unionization data for Korean companies from 1998 to 2008, we document that unionized firms allocate less cash to cash reserves and retirement of external financing than nonunionized firms do. More interestingly, inconsistent with previous findings, we also find that unionized firms utilize a greater portion of cash inflows to investment. This unexpected result of greater investment in unionized firms is in fact consistent with the view that employees are an important nonfinancial stakeholder who naturally cares about the long-term survival of the company; thus, they do not necessarily suppress value-increasing investments. Overall, our findings suggest that researchers need to consider cash flow sensitivities when examining interrelated cash allocation decisions.